Alimentary water-nitrate methemoglobinemia in children in Ternopil region - А.B. Kabakova; A.-M.A. Shulhai; A.-M.A. Shulhai (Zaslavsky O.Yu., 2017)
This article considered the problem of spreading nitrate and nitrite contamination of the water and food, which leads to alimentary water-nitrate methemoglobinemia. Also, we presented the results of our research to show the relevance of methemoglobinemia, to highlight the severity and to propose an effective treatment. Сlinical efficacy of hepatoprotectors in alimentary water-nitrate methemoglobinemia in children of all ages and appropriateness of their use in the treatment of this pathology have been proven.